2020
DOI: 10.1155/2020/3465465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrahigh Temperature Pasteurization on the Liquid Components and Functional Properties of Stored Liquid Whole Eggs

Abstract: Ultrahigh temperature (UHT) pasteurization is often used to sterilize liquid whole eggs in egg processing enterprises in China. Although this treatment generates satisfactory sterilization effect, there are few studies on the processing characteristics and physical and chemical properties of the liquid whole eggs treated by UHT pasteurization. We compared the physical and chemical properties (i.e., foaming ability and stability, emulsification ability and stability, viscosity, thiol content, gel strength, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…The liquid, pasteurized, hot air-dried, and freeze-dried quail eggs were all in compliance with French (FS V08-051) and Canadian (CCS: No.131) standards with a highly satisfactory hygienic quality of 100%, therefore all fit for consumption. The activities of microorganisms in an egg product depend on the nature of the egg product, its initial level of contamination, and especially the temperature [ 22 , 23 ]. James et al [ 15 ] found that baobab pulp from formal processors had significantly lower loads of Enterobacteriaceae , yeasts, and molds than pulp from informal processors.…”
Section: Resultsmentioning
confidence: 99%
“…The liquid, pasteurized, hot air-dried, and freeze-dried quail eggs were all in compliance with French (FS V08-051) and Canadian (CCS: No.131) standards with a highly satisfactory hygienic quality of 100%, therefore all fit for consumption. The activities of microorganisms in an egg product depend on the nature of the egg product, its initial level of contamination, and especially the temperature [ 22 , 23 ]. James et al [ 15 ] found that baobab pulp from formal processors had significantly lower loads of Enterobacteriaceae , yeasts, and molds than pulp from informal processors.…”
Section: Resultsmentioning
confidence: 99%
“…When the temperature of the heat treatment is further increased, the interaction between LDL and the yolk granule components intensifies and initially induces the formation of protein gels [ 26 ]. The enhanced heating conditions can also expose the sulfhydryl groups inside the protein and promote the formation of disulfide bonds, resulting in tighter protein cross-linking and further enhancing the gel strength [ 29 ]. This is the reason for the increasing hardness from SEY to OEY.…”
Section: Discussionmentioning
confidence: 99%
“…La ultra pasteurización (UHT) aplica más calor durante un tiempo muy corto, garantizando una mejor seguridad microbiológica, pero puede afectar la calidad del huevo; además, produce la coagulación de las proteínas, generando pérdidas de la capacidad espumante, emulsionante y gelificante, lo cual también limita su uso como materia prima en la industria alimentaria (Espina et al, 2014). Liu et al (2020), compararon huevos líquidos UHT y no pasteurizados almacenados durante 5 semanas, encontrando que el proceso UHT aumentó la vida útil del producto y mejoraron las propiedades viscosidad, resistencia del gel y solubilidad de las proteínas, principalmente.…”
Section: Mejora La Texturaunclassified